2015
DOI: 10.1007/s40368-015-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release and recharging ability of new dental sealants

Abstract: The three tested sealants exhibited different capabilities to release and uptake fluoride ions after re-fluoridation but significantly lower than the glass ionomer tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…However, extremely high microleakage values greater than those observed in our study have also been reported 16) . Few studies have assessed its additional fluoride-releasing property 6) and pH buffering mechanism 7,8) . Though these cariostatic properties were not measured in this study, its use in clinical settings has to be decided based on weighing both its physical and cariostatic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extremely high microleakage values greater than those observed in our study have also been reported 16) . Few studies have assessed its additional fluoride-releasing property 6) and pH buffering mechanism 7,8) . Though these cariostatic properties were not measured in this study, its use in clinical settings has to be decided based on weighing both its physical and cariostatic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The application of self-etching adhesives instead of acid etching might simplify the clinical workflow, reduce application times and achieve acceptable cooperation from children. Most recently, a new product (BeautiSealant, Shofu, Kyoto, Japan) featuring reduced working time and fluoride-releasing and pH-buffering properties was released on the dental market [6][7][8] . Stringent testing of new materials is imperative before formulating clinical recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The material was infused into the Teflon mold and pressed between two glass slabs with a transparent matrix in between and allowed to set inside the mold for 7 min through chemical curing[ 3 ] or light cured (Elipar, wavelength 430–480 nm; light intensity 1200 mW/cm 2 , 3M ESPE, St. Paul, MN 55144-1000 USA 1-800-634-2249) through the glass slides for 40 s on both the surfaces. Specimens were taken out of the Teflon mold and light cured for 40 s on the sides[ 2 ] and stored at 37°C in 100% humidity for 24 h and later transferred into polyethylene containers containing 10 ml of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…It was finally allowed to set [3]. Similar methodology was adopted for RMGIC and Cention N with an additional step of light curing, where the samples were light-cured from the top as well as from the bottom for 20 seconds using LED light-curing unit (Blue phase, Ivoclar Vivadent AG, Schaan, Liechtenstein) emitting blue light with intensity of 1200 Mw/cm² and wavelength of 430-480 nm [5].…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Resin modified glass ionomer cement (RMGIC), also called light cure glass ionomer cement was developed to overcome some of the disadvantages of conventional GIC. According to various studies, RMGIC has more flexural strength when compared to conventional GIC [3].…”
Section: Introductionmentioning
confidence: 99%